Psychological Burnout Among Middle School Teachers - A Field Study in the City of Aflou - - Derderi, Moussa (Journal of Ecohumanism, 2026)
This research aimed to investigate psychological burnout among a sample of middle school teachers in the city of Aflou and its relationship with the following variables: age, specialization, and professional rank. The study sample consisted of (65) teachers during the academic year (2023-2024). The descriptive method, appropriate for this study, was employed, relying on the Maslach Burnout Inventory (MBI); furthermore, the researcher utilized statistical processing (SPSS V21), which included statistical methods, percentages, arithmetic means, and standard deviations. The obtained results were as follows: The level of psychological burnout among middle school teachers in the city of Aflou was low. There is no statistically significant correlational relationship in the level of psychological burnout among the sample individuals attributable to the age variable. There are no statistically significant differences in the level of psychological burnout among the sample individuals attributable to the specialization variable. There are no statistically significant differences in the level of psychological burnout among the sample individuals attributable to the professional rank variable.